The Big Split : Why Did Output Trajectories in the ASEAN-4 Diverge after the Global Financial Crisis? - Isnawangsih, Agnes (IMF Working Papers; Working Paper, 2013)
The global financial crisis originated in advanced economies, but had a major impact on emerging markets. The impact, however, was not uniform. Even in a relatively homogenous group of countries such as ASEAN-4 (Indonesia, Malaysia, the Philippines and Thailand), there were considerable differences both in terms of instantaneous impact of the crisis and in terms of output performance relative to trend. There are several main reasons for the divergence. First, trade shocks had a larger impact on more open economies (Malaysia and Thailand). Second, countercyclical fiscal stimulus in Indonesia and the Philippines was larger and was sustained longer. Third, idiosyncratic factors pushed output up in Indonesia and down in Thailand. Such factors include investment-friendly structural reforms and fortuitously timed election spending in Indonesia, as well as political instability and natural disasters in Thailand.